Prevalence of Anemia in Khulna, Bangladesh and Comparative Study among Available Hemantinic Preparations (Stamford Journal of Pharmaceutical Sciences, 2011)
DOI: http://dx.doi.org/10.3329/sjps.v3i2.8038 S.J. Pharm. Sci 3(2): 49-50